Tuberculosis-related knowledge, attitude and preventive practices among abattoir workers in Gusau, Nigeria - Gusau, Ismaila Usman (2016)
Introduction: Tuberculosis (TB) is still a major health concern worldwide. The global burden of TB is estimated to be 8.5 to 9.2 million with 1.2 to 1.5 million deaths annually. Asia and Africa are affected with 57% and 26% of the disease burden respectively. Nigeria ranked third among the world’s six countries with high burden of TB and has the highest estimated number of new cases with nearly 590,000 new cases annually. Nigeria is one of the African countries where bovine TB is wide spread in both cattle and humans. Although, the current status on the actual prevalence rate of bovine TB at the national level is unknown but from the limited surveys conducted by some researchers reported that, the prevalence of TB due to M. bovis is up to 14%. The isolation and identification of M. bovis in fresh and sour milk sold at local markets, sputum and tissue samples from humans especially herdsmen, abattoir and slaughter houses has been reported. This indicates that the disease occurs both in cattle and humans in Nigeria. Thus, reason to assess the knowledge, attitude and practices of abattoir workers on TB. Objectives: To determine the level of knowledge, attitude and preventive practices on tuberculosis among abattoir workers in Gusau, Zamfara State, Nigeria. Methodology: A cross-sectional study was conducted in Gusau Modern Abattoir, Zamfara State, Nigeria. The abattoir was chosen because it is the only one in the state. A total of 416 eligible abattoir workers were selected using proportionate stratified random sampling. Data was collected on knowledge, attitude and preventive practices on TB among the abattoir workers from May to July 2014, through face to face interview and self-administered questionnaire, which was validated by content and face validities. Reliability was measured by checking the internal consistency using Cronbach’s alpha and values above 0.7 were accepted. Descriptive analysis, chi-square and multivariate logistic regression were conducted. Significant level (p) was set at 0.05. Results: The response rate was 91.3%, the overall mean knowledge score of the respondents was 29.76 (SD) 14.15, with 53.2% having high knowledge and 46.8% having low knowledge on TB. However, 52.9%, mean (SD) is 42.76 (6.23) of the respondents have positive attitude and 58.7%, mean (SD) is 9.13 (4.50) practices preventive measures towards TB. Predictors of knowledge, attitude and preventive practices were determined using logistic regression analysis and results from Chisquare tests with p < 0.25 were included. Years of working experience (AOR = 1.98; CI = 1.231 – 3.189), TB screening (AOR = 3.04; CI = 1.446 – 6.419) and family member history of TB infection (AOR = 17.35; CI = 2.274 – 132.421) were found to be the predictors of knowledge on TB. Immunization (AOR = 2.45; CI = 1.279 – 4.688) and training (AOR = 4.60; CI = 2.254 – 9.385) were found to be the predictors of attitude towards TB. For preventive practices, history of TB infection (AOR = 5.21; CI = 1.547 – 17.560) and family member history of TB infection (AOR = 3.54; CI = 1.330 – 9.429) were found to be the predictors of preventive practices regarding TB. Conclusion: This study has identified that there is low level of knowledge, negative attitude and poor preventive practices on TB among abattoir workers in Zamfara State. However, predictors of knowledge on TB were years of working experience, TB screening and family member infected with TB. Predictors of attitude towards TB were immunization and training. Predictors of TB preventive practices were personal and family member infected with TB. The study findings will help in development of interventional programs for efficient control of TB (human and animal).